Movement and thermal niche of the first satellite‐tagged Mediterranean spearfish (Tetrapturus belone). (14th November 2018) - Arostegui, Martin C.; Braun, Camrin D.; Gaube, Peter
Abstract: The Mediterranean spearfish ( Tetrapturus belone ) is one of the least‐studied istiophorid billfishes, with little known of its biology, ecology, and behavior. To assess the species' movement and thermal niche, we analyzed telemetry data from, to our knowledge, the first and only Mediterranean spearfish ever outfitted with a pop‐up satellite archival transmitting tag. Throughout a 29‐day deployment during July and August 2015, the fish travelled in Italian waters of the Tyrrhenian and Ligurian Seas, spending on average 93% of each 24‐hr period above 30 m and exhibiting a diel activity pattern comprised of daytime vertical movement and nighttime near‐surface residency. The preferred thermal niche was 26–28°C, but the spearfish experienced temperatures as low as 14.2°C during descents. Vertical distribution was limited throughout the deployment with more time spent at depth in areas where the thermocline was comparatively deeper and weaker, consistent with habitat compression experienced by other billfishes.